UPAYA MENINGKATKAN KEMAMPUAN MEMAHAMI TEKS DENGAN TEKNIK SQ3R (SURVEY-QUESTION-READ-RECITE-REVIEW) SISWA KELAS XII TKJ A SMK NEGERI 1 KEBONSARI KABUPATEN MADIUN TAHUN PELAJARAN 2011/2012 - Elfi Ida Istiqomah (IKIP PGRI MADIUN, 2015)
Language occurs and lives in a context that influence anything, determine and link to the choices of someone's language when creating and interpreting texts. In any context, people use language to perform three main functions: Ideational function, the function of language to express or construct ideas or information; Interpersonal function, the function of language to interact with others who express speech, attitudes, feelings etc.; Textual function, the function that regulates how the text is created in order to achieve it’s cohesion and coherence, so it will easily understood those who hear or read it. Problem statement of this research: Is there an ability increasing in understanding the text with SQ3R reading techniques (Survey-Question-Read-Recite-Review) in TKJ A to the twelfth grade students of SMK Negeri 1 Kebonsari Madiun in the School Year 2011/2012? In this study, researchers collaborate with other teachers and the principals. Researchers involved in the study from the beginning to the end of the study. Researchers are trying to see, observe, feel, live, reflect and evaluate learning activities that take place. The stages of research consists of planning, acting, observing and reflecting. The study collected data were statistically analyzed using the formula that is mean or average to get accurate results. The result showed that the average value of the cycle has increased significantly. The conclusion of the result is: an ability increasing in understanding the text with SQ3R reading techniques (Survey-Question-Read-Recite-Review) in TKJ A to the twelfth grade students of SMK Negeri 1 Kebonsari Madiun in the School Year 2011/2012.